2014
DOI: 10.1371/journal.pone.0104517
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Nitrate in Intertidal Permeable Sediments

Abstract: Coastal zones act as a sink for riverine and atmospheric nitrogen inputs and thereby buffer the open ocean from the effects of anthropogenic activity. Recently, microbial activity in sandy permeable sediments has been identified as a dominant source of N-loss in coastal zones, namely through denitrification. Some of the highest coastal denitrification rates measured so far occur within the intertidal permeable sediments of the eutrophied Wadden Sea. Still, denitrification alone can often account for only half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
73
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 74 publications
(99 reference statements)
11
73
3
Order By: Relevance
“…The denitrification rates measured in the present study spanned the range of flow-through reactor rates (∼< 1-32 µmol L −1 h −1 ) previously observed in silicate sands (Evrard et al, 2013;Kessler et al, 2012;Marchant et al, 2014;Rao et al, 2007). The availability, and composition, of organic matter is expected to be a key factor controlling potential denitrification rates (Eyre et al, 2013a;Seitzinger, 1988), and the importance of this in permeable sediments has also been recently underscored by Marchant et al (2016), who observed a strong relationship between potential denitrification rate and sediment oxygen consumption.…”
Section: Comparison Of Potential Denitrification Rates With Previous supporting
confidence: 66%
“…The denitrification rates measured in the present study spanned the range of flow-through reactor rates (∼< 1-32 µmol L −1 h −1 ) previously observed in silicate sands (Evrard et al, 2013;Kessler et al, 2012;Marchant et al, 2014;Rao et al, 2007). The availability, and composition, of organic matter is expected to be a key factor controlling potential denitrification rates (Eyre et al, 2013a;Seitzinger, 1988), and the importance of this in permeable sediments has also been recently underscored by Marchant et al (2016), who observed a strong relationship between potential denitrification rate and sediment oxygen consumption.…”
Section: Comparison Of Potential Denitrification Rates With Previous supporting
confidence: 66%
“…O 2 consumption rates of surface sediments (upper 5 cm) from sites 3 and 2 were determined after Marchant et al (2014) using flow through columns of 10 cm diameter and 20 cm length. The flow through columns were filled with sand while completely submerged in seawater to prevent the trapping of air bubbles.…”
Section: Oxygen Concentrations and Consumption Ratesmentioning
confidence: 99%
“…The latter were shown to be of great importance for carbon, nutrient, and trace metal cycles in the large tidal flat area called Wadden Sea stretching from the Netherlands to Denmark, and the frequent water exchange between tidal flat areas and the North Sea transport carbon, nutrient, and trace metals to coastal waters of the North Sea (e.g. Beck et al, 2008;Billerbeck et al, 2006;Grunwald et al, 2010;Marchant et al, 2014;Moore et al, 2011;Riedel et al, 2011;Røy et al, 2008;Santos et al, 2015). Pore water discharge rates calculated for nearby sandy Wadden Sea sediments vary depending on the method applied and the sediment depth considered Moore et al, 2011;Riedel et al, 2010), among which the method most comparable to the model approach applied in our study resulted in lower flux rates (0.97 m −3 per tide and meter of shoreline, which equals~2 m −3 per day and meter of shoreline; Riedel et al, 2010) compared to our study.…”
Section: Pore Water Discharge Influences Phytobenthos and Nearshore Wmentioning
confidence: 99%
“…So far, the impact of pore water advection on biogeochemistry and pore water constituent effluxes from permeable sediments has mostly been studied in microtidal sheltered beaches (Beck et al, ; Gonneea & Charette, ; Liu et al, ; O'Connor et al, ; Santos et al, ), tidal flat areas (Beck et al, ; Billerbeck et al, ; Gao et al, ; Huettel & Rusch, ; Marchant et al, ; Riedel et al, ), or subtidal sediments (Ahmerkamp et al, ; Marchant et al, ; Shum & Sundby, ), which are exposed to a lower wave energy level than high energy beaches. In contrast, only few studies have been conducted at wave exposed mesotidal to macrotidal sites like the French Aquitanian coast (Anschutz et al, ; Charbonnier et al, ; Charbonnier et al, ) or the beaches of Spiekeroog Island, Germany (Beck et al, ; Reckhardt et al, ; Seidel et al, ; Waska et al, ).…”
Section: Introductionmentioning
confidence: 99%